How Wide and High can Polyhedral Liquid Marbles be Fabricated? - Hayashi, Masaki; Manabe, Hikaru; Hirai, Tomoyasu; Nakamura, Yoshinobu; Fujii, Syuji (Advanced materials interfaces, 2024)
Liquid marbles (LMs) are liquid droplets in gaseous phase, which are generally millimeter size, coated by solid particles. In this study, how wide and high LMs can be fabricated is investigated. Polyhedral LMs are fabricated using polymer plates with millimeter to meter sizes as a stabilizer and water as an inner liquid. Rectangular LMs with widths exceeding 1 m, the largest width ever reported, can be successfully fabricated. The height of the LMs is found to be subject to restriction by the hydrostatic pressure and cubic LMs with heights of up to 5 mm, which is the maximum height limit for LMs stabilized with nano/micrometer‐sized particles, are fabricated. Reduction of the hydrostatic pressure by changing the LM shape from cube to pyramid and introduction of particle‐stabilized bubble into the LM enabled the increase of height of the LM up to 9.8 mm, the highest height ever reported. Investigation using non‐aqueous liquids as an inner liquid confirmed that the longer the capillary length, the higher the maximum possible height of LMs. Finally, the polyhedral LMs are demonstrated to function as a microreactor for silver mirror reaction and chemical oxidative polymerization, resulting in the formation of Janus polymer plates. How wide and high polyhedral liquid marbles (LMs) can be fabricated is investigated. Rectangular LMs with widths exceeding 1 m, the largest width ever reported, can be fabricated. Reduction of hydrostatic pressure by changing the LM shape and introduction of bubble into the LM enabled the increase of LM heights up to 9.8 mm, the highest height ever reported.